2000
DOI: 10.1523/jneurosci.20-16-05965.2000
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptors in Müller Glial Cells from the Human Retina

Abstract: ATP has been shown to be an important extracellular signaling molecule. There are two subgroups of receptors for ATP (and other purines and pyrimidines): the ionotropic P2X and the G-protein-coupled P2Y receptors. Different subtypes of these receptors have been identified by molecular biology, but little is known about their functional properties in the nervous system. Here we present data for the existence of P2 receptors in Müller (glial) cells of the human retina. The cells were studied by immunocytochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(158 citation statements)
references
References 41 publications
(46 reference statements)
10
148
0
Order By: Relevance
“…The membrane permeability to large cations has been shown to be much lower in the human than in the rat receptor, and ATP-triggered dye uptake in cells transfected with the human receptor or in human macrophages is only 20% of that observed in cells transfected with the rat receptor. Similar results have recently been reported for human retinal Müller cells, which share properties in common with astrocytes and have been shown to express P2X 7 by RT-PCR, immunocytochemistry, and electrophysiology but do not form a pore in response to BzATP (Pannicke et al, 2000). It has been suggested that the species-specific differences observed in the properties of P2X 7 may reflect differences in the C-terminal domain of the human versus the rat receptor (Rassendren et al, 1997).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The membrane permeability to large cations has been shown to be much lower in the human than in the rat receptor, and ATP-triggered dye uptake in cells transfected with the human receptor or in human macrophages is only 20% of that observed in cells transfected with the rat receptor. Similar results have recently been reported for human retinal Müller cells, which share properties in common with astrocytes and have been shown to express P2X 7 by RT-PCR, immunocytochemistry, and electrophysiology but do not form a pore in response to BzATP (Pannicke et al, 2000). It has been suggested that the species-specific differences observed in the properties of P2X 7 may reflect differences in the C-terminal domain of the human versus the rat receptor (Rassendren et al, 1997).…”
Section: Discussionsupporting
confidence: 80%
“…Additional imaging experiments in our laboratory using the calcium-sensitive dye fura-2 demonstrated that these cells also respond to BzATP, a P2X 7 -selective agonist, which at a concentration of 300 M elicited an increase in [Ca 2ϩ ] i in Ͼ95% of astrocytes (data not shown). Similar responses to BzATP have been observed previously in other human cell types expressing the P2X 7 receptor, including retinal Müller cells and cells of the monocytemacrophage lineage (Rassendren et al, 1997;Pannicke et al, 2000). Reverse transcription (RT)-PCR using specific primers Figure 2.…”
Section: Extracellular Atp Differentially Regulates Il-1␤-induced Expsupporting
confidence: 65%
“…BzATP can stimulate P2X 1 , P2X 3 , and P2Y receptors as well (Bianchi et al, 1999;Pannicke et al, 2000). However, we have shown previously that the rat retina does not express P2X 1 (Braendle et al, 1998a).…”
Section: Pharmacology Of P2x 7 Receptormentioning
confidence: 73%
“…Moreover, stimulation of retinal glial cells in situ evokes an increase in extracellular ATP, accompanied by the spreading of a calcium wave among adjacent glial cells; this in turn affects the firing rate of neighboring neurons (Newman andZahs, 1997, 1998;Newman, 2001). Primary culture preparations have made it possible to identify cholinergic neurons, retinal ganglion cells (RGCs), astrocytes, Muller cells, and oligodendrocytes as cellular targets of extracellular ATP (Neal and Cunningham, 1994;Kirischuk et al, 1995;Keirstead and Miller, 1997;Newman andZahs, 1997, 1998;Neal et al, 1998;Taschenberger et al, 1999;Pannicke et al, 2000). We performed a first systematic study of the expression and distribution of different types of ATP receptors in the retina and found that both P2X and P2Y subunits are expressed in identified adult retinal cell types, such as bipolar cells, Muller cells, and RGCs (Braendle et al, 1998a,b;Jabs et al, 2000;Wheeler-Schilling et al, 2000, 2001.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various gliotransmitters in astrocytes treated with SW-CNTs or MW-CNTs have increasing uptake or release. Some studies have shown that ATP-induced stimulation of P2X7 receptors releases not only ATP and glutamate, but also GABA from astrocytes of the brain or Muller cells of the retina [59]. Gliotransmitters in astrocyte-affected CNTs have an active effect on neurodegenerative disease and neuron–glia crosstalk by transporter, signaling factor and receptor.…”
Section: Discussionmentioning
confidence: 99%